AN IDENTIFICATION OF ANGIOSPERMS IN KEMBANG NATURE RESERVE, JEPARA REGENCY - Maila Shofa Maghfiroh; Enni Suwarsi Rahayu; Talitha Widiatningrum (Universitas Medan Area, 2023)
Based on the diversity of angiosperms which are widespread throughout the world and play an important role, identification is necessary, especially in flora reserves. This study aims to determine the type of angiosperms in the Kembang Nature Reserve, Jingotan Village, Kembang District, Jepara Regency. The method used in this research was the shipping method from Pal 2 to Pal 6 of the Kembang Nature Reserve cruise line using a purposive sampling technique. The results of the study found that 30 angiosperms, 9 species from the monocot class and 21 species from the dicot class. The monocot class includes 9 species: Vanilla planifolia, Ottochloa nodosa, Zingiber zerumbet, Arenga pinata, Salacca zalacca, Tacca palmata, Costus speciosus, Amorhophallus variabili, and Amorphophallus muelerri Blume. 21 species belonging to the class of dicots, namely Tectona grandis, Clerodendrum japonicum, Lantana camara, Leea indica, Sauropus androgynus, Elephantopus sp., Paederia foetida, Cyclea barbata, Anacardium occidentale, Dracontomelon dao, Mangifera indica, Teucapera cubeba, Cocephala, Clerodendrum infortunatum, Ficus septica, Artocarpus altilis, Cinnamomum iners, Dysoxylum densiflorum, Dysoxylum gaudichaudianum, and Dysoxylum densiflorum.